Firm life cycle and idiosyncratic volatility - Hasan, Mostafa; Habib, A. (Elsevier BV, 2016)
This paper investigates the association between idiosyncratic volatility and firm life cycle stages. Since firm performance and availability of information vary across life cycle stages, and such variation affects uncertainty about future cash flows and stock returns, we argue that idiosyncratic volatility also varies across firm life cycle stages. Using US data, this study shows that idiosyncratic volatility is significantly higher in the introduction and decline stages, and significantly lower in the growth and mature stages, when compared to that in the shake-out stage. Our study also reveals that the roles of both cash flow volatility and information uncertainty in affecting idiosyncratic volatility vary depending on firm life cycle stages. Our results are robust to alternative specifications of life cycle proxies and idiosyncratic volatility, and to an alternative regression specification.